Evaluation of risk stratification program based on trajectories of functional capacity in patients with acute coronary syndrome: The REACP study - Li, Dongze; Chen, Xiaoli; Li, Fanghui; Jia, Yu; Li, Zhilin; Liu, Yi; Ye, Lei; Gao, Yongli; Zhang, Wei; Li, Hong; Zeng, Rui; Wan, Zhi; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background As a validated assessment tool for functional disability (activities of daily living), the Barthel index (BI) assessed initially at admission has the potential to stratify patients with high-risk acute coronary syndrome (ACS). Dynamic trajectory evaluation of functional capacity in hospitals may provide more prognostic information. We aimed to establish a novel dynamic BI-based risk stratification program (DBRP) during hospitalization to predict outcomes among ACS patients. Methods A total of 2,837 ACS patients were included from the Retrospective Multicenter Study for Early Evaluation of Acute Chest Pain. The DBRP rating (low, medium, and high-risk categories) was calculated from dynamic BI at admission and discharge. The primary outcome was all-cause mortality, and the secondary outcome was cardiac mortality. Results Of all the included patients, 312 (11%) died during a median follow-up period of 18.0 months. Kaplan–Meier analysis revealed that the cumulative mortality was significantly higher in patients in the higher risk category according to the DBRP. Multivariable Cox regression analysis indicated that, compared to the low-risk category, the higher risk category in the DBRP was an independent strong predictor of all-cause mortality after adjusting for confounding factors (medium-risk category: hazard ratio [HR]: 1.756, 95% confidence interval [95% CI]: 1.214–2.540; P = 0.003; high-risk category: HR: 5.052, 95% CI: 3.744–6.817; P < 0.001), and the same result was found for cardiac mortality. Conclusion The DBRP was a useful risk stratification tool for the early dynamic assessment of patients with ACS. Clinical trial registration [http://www.chictr.org.cn], identifier [ChiCTR1900024657].